Phasic left atrial strain analysis to discriminate cardiac amyloidosis in patients with unclear thick heart pathology. (3rd April 2020) - Brand, Anna; Frumkin, David; Hübscher, Anne; Dreger, Henryk; Stangl, Karl; Baldenhofer, Gerd; Knebel, Fabian
Abstract: Aims : Traditional echocardiographic parameters for the assessment of suspected cardiac amyloidosis (CA) are of limited diagnostic accuracy. We sought to explore differences and the discriminative value of phasic left atrial strain (LAS) reductions and of regional longitudinal left ventricular (LV) strain alterations (relative apical sparing; RELAPS) in CA and other causes of LV wall thickening (LVH). Methods and results : We included 54 patients with unclear LVH (mean septal diastolic wall thickness 17.8 ± 3.5 mm); CA was bioptically confirmed in 35 patients (8 mATTR, 6 wtATTR, 20 AL, and 1 AA amyloidosis) and LVH in 19 subjects. We analysed RELAPS as well as LA reservoir (LASr), conduit (LAScd), and contraction strain (LASct) using 2D speckle tracking echocardiography (EchoPAC software, GE). RELAPS was higher (1.37 ± 0.94 vs. 0.86 ± 0.29, P < 0.007), whereas atrial mechanics were significantly reduced in CA (LASr, LAScd, and LASct: 9.7 ± 5.2%, −6.5 ± 3.5%, and −5.0 ± 4.1% in CA; and 22.7 ± 7.8%, −13.9 ± 5.2%, and −13.0 ± 5.5% in LVH, respectively; P < 0.001 each). With an area under the curve (AUC) of 0.91 [95% confidence interval (CI) 0.82–0.99], LASr showed a higher diagnostic accuracy in discriminating CA than RELAPS (AUC 0.74, 95% CI 0.59–0.88). LASr and LAScd remained significantly associated with CA in a multivariate regression model. Conclusion : Phasic LAS was significantly reduced in patients with CA and showed a higher diagnostic accuracy in discriminating CA than RELAPS. The additional assessment of phasic LAS may be useful to rule in the possible diagnosis of CA in patients with unclear LVH.